PENGARUH PRODUK DOMESTIK BRUTO (PDB) DAN SUKU BUNGA DEPOSITO BERJANGKA 1 BULAN TERHADAP JUMLAH SIMPANAN DEPOSITO BERJANGKA 1 BULAN PADA BANK CENTRAL ASIA (BCA) DI INDONESIA TAHUN 2010-2019 - Shadiq Fikri; Mayes Anthony; Richard Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine whether there an influence of gross domestic product and 1-month time deposite interest rate on the amount of 1-month time deposit at Bank Central Asia in Indonesia period 2010-2019. This study uses secondary data obtained from approved financial statement data, namely the official website of Bank Central Asia and Bank Indonesia from 2010 to 2019. In this study using the Ordinary Least Square (OLS) method to find out changes in the value of the dependent variable namely Number of Deposits of 1 Month Time Deposit (Y) supported by the independent variable Gross Domestic Product (X1) and Interest Rate of 1 Month Time Deposit (X2) using multiple linear regression techniques with eviews program 10. This study consists of two independent variables (domestic product and one-month time deposit interest rates) and the dependent variable (the number of 1-month time deposit deposits). The results obtained are gross domestic product and 1-month time deposit interest rate simultaneously against the amount of 1-month time deposit deposits at Bank Central Asia in Indonesia with a significant level of 5% obtained from the value of the requirement of F Statistics <α (0.05), namely 0, 000071 <α (0.05). Partially, gross domestic product and 1-month time deposit rates have been approved positively and significantly to the amount of 1-month time deposits at Bank Central Asia in Indonesia. The second independent variable is free in explaining the independent variable with the adjusted value of R-Square 0.916072. This means that contributing to the second, the independent variable on the variable, which is equal to 91.61% while the remaining 8.39% is needed by other factors outside this study.Keywords: Gross Domestic Product, Deposit Interest Rate, 1 Month Time Deposit